1998
DOI: 10.1111/j.1465-7287.1998.tb00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Indexed Bonds and Heterogeneous Agents

Abstract: The widespread belief that one can read off the public's expectations of inflation from the yield differential between indexed and conventional bonds ignores the fact that indexed bonds are held largely by those who expect the most inflation. However, holding indexed bonds as a hedge against inflation implies that such bonds have the advantage of being a relatively cheap source of funds. Copyright 1998 Western Economic Association International.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Aizenman and Guidotti [1994] developed a two-period model with costly taxation and demonstrated that capital controls may aid in reducing the cost of recycling the domestic debt. Mayer [1998] demonstrates that debt indexing will result in lower Treasury interest costs even when agents are heterogeneous in their inflationary expectations. Beetsma [1996] considers the role of expectations in a model with poor and wealthy agents and concludes that in the absence of repudiation, indexed debt would generate a first-best outcome.…”
Section: Strategic Cash Reserve Changesmentioning
confidence: 97%
See 1 more Smart Citation
“…Aizenman and Guidotti [1994] developed a two-period model with costly taxation and demonstrated that capital controls may aid in reducing the cost of recycling the domestic debt. Mayer [1998] demonstrates that debt indexing will result in lower Treasury interest costs even when agents are heterogeneous in their inflationary expectations. Beetsma [1996] considers the role of expectations in a model with poor and wealthy agents and concludes that in the absence of repudiation, indexed debt would generate a first-best outcome.…”
Section: Strategic Cash Reserve Changesmentioning
confidence: 97%
“…Beetsma [1996] considers the role of expectations in a model with poor and wealthy agents and concludes that in the absence of repudiation, indexed debt would generate a first-best outcome. Mayer [1998] notes that in January 1997, the U.S. joined the list of countries that issue indexed bonds. However, Evans [1997] notes that only 15.57 percent of the marketable debt is denominated in bonds with maturities of 10 or more years, although 60.8 percent of the marketable debt is f'manced with 2-, 3-, and 5-year rates where indexing may play a somewhat diminished role due to the shorter maturity dates.…”
Section: Strategic Cash Reserve Changesmentioning
confidence: 98%